Hypofractionated Post-Prostatectomy Radiotherapy in 16 Fractions: A Single-Institution Outcome - Pavol Dubinsky; Vladimir Vojtek; Katarina Belanova; Natalia Janickova; Noemi Balazova; Zuzana Tomkova (Life, 2023)
Background: The optimal hypofractionated schedule of post-prostatectomy radiotherapy remains to be established. We evaluated treatment outcomes and toxicity of moderately hypofractionated post-prostatectomy radiotherapy in 16 daily fractions delivered with intensity-modulated radiotherapy. The treatment schedule selection was motivated by limited technology resources and was radiobiologically dose-escalated. Methods: One hundred consecutive M0 patients with post-prostatectomy radiotherapy were evaluated. Radiotherapy indication was adjuvant (ART) in 19%, early-salvage (eSRT) in 46% and salvage (SRT) in 35%. The dose prescription for prostate bed planning target volume was 52.8 Gy in 16 fractions of 3.3 Gy. The Common Terminology Criteria v. 4 for Adverse Events scale was used for toxicity grading. Results: The median follow-up was 61 months. Five-year biochemical recurrence-free survival (bRFS) was 78.6%, distant metastases-free survival (DMFS) was 95.7% and overall survival was 98.8%. Treatment indication (ART or eSRT vs. SRT) was the only significant factor for bRFS (HR 0.15, 95% CI 0.05–0.47, p = 0.001) and DMFS (HR 0.16, 95% CI 0.03–0.90; p = 0.038). Acute gastrointestinal (GI) toxicity grade 2 was recorded in 24%, grade 3 in 2%, acute genitourinary (GU) toxicity grade 2 in 10% of patients, and no grade 3. A cumulative rate of late GI toxicity grade ≥ 2 was observed in 9% and late GU toxicity grade ≥ 2 in 16% of patients. Conclusions: The observed results confirmed efficacy and showed a higher than anticipated rate of early GI, late GI, and GU toxicity of post-prostatectomy radiobiologically dose-escalated hypofractionated radiotherapy in 16 daily fractions.